2021
DOI: 10.1155/2021/9218137
|View full text |Cite
|
Sign up to set email alerts
|

A Real‐Time Object Detector for Autonomous Vehicles Based on YOLOv4

Abstract: Object detection is an important part of autonomous driving technology. To ensure the safe running of vehicles at high speed, real-time and accurate detection of all the objects on the road is required. How to balance the speed and accuracy of detection is a hot research topic in recent years. This paper puts forward a one-stage object detection algorithm based on YOLOv4, which improves the detection accuracy and supports real-time operation. The backbone of the algorithm doubles the stacking times of the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Readers should note that the tables use the accuracy parameter as a representation of system performance (the same method was used in similar papers, e.g. [56]), but there are other parameters (such as IoU) that may give different insights into the system's functioning but were not used to report results in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Readers should note that the tables use the accuracy parameter as a representation of system performance (the same method was used in similar papers, e.g. [56]), but there are other parameters (such as IoU) that may give different insights into the system's functioning but were not used to report results in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…To objectively validate the target identification performance of the proposed method in this research, the suggested method is compared to some advanced methods on the BDD-IW dataset under identical settings. Among these techniques are Faster R-CNN (Girshick, 2015 ), SSD (Liu et al, 2016 ), YOLOv3 (Redmon and Farhadi, 2018 ), YOLOv4 (Bochkovskiy et al, 2020 ), YOLOv5 (Ultralytics), YOLOv6 (Li et al, 2022 ), YOLOX (Ge et al, 2021b ), RT-YOLOv4 (Wang R. et al, 2021 ), TPH-YOLOv5 (Zhu et al, 2021 ), and PPYOLOE (Xu et al, 2022 ). The BDD-IW dataset comparison findings are displayed in Table 3 .…”
Section: Designs For Experimentsmentioning
confidence: 99%
“…This section offers a brief survey of existing object recognition models in autonomous systems. In [11], a one-phase object recognition method based on YOLOv4 enhances the recognition performance and supports real-time processes. The neck approach substitutes the SPP with the RFB framework, enhances the PAN framework of the feature fusion method, includes the attention Convolution Block Attention Module (CBAM) and CA architecture to neck and backbone architecture, and lastly, minimizes the complete network width.…”
Section: Related Workmentioning
confidence: 99%